Characterization of Tg(Etv4-GFP) and Etv5RFP Reporter Lines in the Context of Fibroblast Growth Factor 10 Signaling During Mouse Embryonic Lung Development - Jones, Matthew R.; Lingampally, Arun; Dilai, Salma; Shrestha, Amit; Stripp, Barry; Helmbacher, Francoise; Chen, Chengshui; Chao, Cho-Ming; Bellusci, Saverio (Frontiers in Genetics, 2019)
Members of the PEA3 transcription factors are emerging as bone fide targets for fibroblast growth factor (FGF) signalling. Among them, ETV4 and ETV5 appear to mediate FGF10 signalling during early embryonic lung development. In this paper, recently obtained Tg(Etv4-GFP) and Etv5CreERT2-RFP fluorescent reporter lines were generally characterized during early embryonic development and in the context of FGF10 signalling, in particular. We found that both Tg(Etv4-GFP) and Etv5CreERT2-RFP were primarily expressed in the epithelium of the lung during embryonic development. However, the expression of Etv5CreERT2-RFP was much higher than that of Tg(Etv4-GFP), and continued to increase during development, whereas Tg(Etv4-GFP) decreased. The expression patterns of the surrogate fluorescent protein GFP and RFP for ETV4 and ETV5, respectively, agreed with known regions of FGF10 signalling in various developing organs, including the lung, where ETV4-GFP was seen primarily in the distal epithelium and to a lesser extent in the surrounding mesenchyme. As expected, ETV5-RFP was restricted to the lung epithelium, showing a decreasing expression pattern from distal buds to proximal conducting airways. FGF10 inhibition experiments confirmed that both Etv4 and Etv5 are downstream of FGF10 signalling. Finally, we also validated that both fluorescent reporters responded to FGF10 inhibition in vitro. In conclusion, these two reporter lines appear to be promising tools to monitor FGF10/FGFR2b signalling in early lung development. These tools will have to be further validated at later stages and in other organs of interest.